GAMBARAN TINGKAT DEPRESI PADA PRIA USIA 30-50 TAHUN YANG MENGALAMI ANDROPAUSE DI KECAMATAN TEMBALANG KOTA SEMARANG (STUDI DI KECAMATAN TEMBALANG) - Winda Apriani; Ari Udiyono; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Andropause is a decrease in testosterone levels in men which is a natural process that occurs with age and all men must suffer from andropause. In men, andropause conditions can cause various symptoms, one of the is depression. Decreasing in testosterone levels affect the hormone serotonin as an antidepressant resulting in the onset of depression. This study is to describe the level of depression in men aged 30-50 years who experienced Andropause in District Tembalang. this study is a descriptive study, with cross sectional study design. Sampling by Propotional Random Sampling with total sample of 100 respondents based on formula of estimation of proportion with known population. The result showed 64 respondents who had andropause were 64 (64%), as many as 36 (56.2%) of respondents who had experienced andropause also experienced depression while 28 (48.3%) respondents did not experience depression. In addition, Respondents who experienced andropause symptoms showed a positive relationship toward depression status. Depression levels of respondents experiencing andropause most experienced a mild depression 28 (87,5%), whereas in respondents who didn’t experience andropause more not depressed by 30 (51.7%). Results indicated men who have andropause may experience depressive symptoms more severe, compared with men without andropause. Therefore, herefore, men who are already active andropause age can prevent and suffer as early as possible by doing a healthy lifestyle such as regular exercise, maintaining a balanced diet, enough rest, reduce alcohol and can minimize the risk of depression, in addition health workers can optimize posyandu elderly as a place of information andropause and health of elderly men.